2019
DOI: 10.1155/2019/7386734
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67 Expression is a Significant Prognostic Factor Only When Progesterone Receptor Expression is Low in Estrogen Receptor-Positive and HER2-Negative Early Breast Cancer

Abstract: Objective. While the value of Ki-67 has been recognized in breast cancer, controversy also exists. The goal of this study is to show the prognostic value of Ki-67 according to progesterone receptor (PgR) expression in patients who have estrogen receptor- (ER-) positive, human epidermal growth factor receptor 2- (HER2-) negative early breast cancer. Methods. The records of nonmetastatic invasive breast cancer patients who underwent surgery at a single institution between 2009 and 2012 were reviewed. Primary end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…When the critical value of Ki-67 index was 10%, for both high expression (≥10%) and low expression (<10%), patients with BC show statistical differences in OS and recurrence-free survival (RFS) when there's low PR expression (<20%). In particular, patients with high Ki-67 expression and low PR expression had the poorest prognosis [20]. Similarly, Ki-67 index is signi cant to DFS judgment of patients with BC.…”
Section: Discussionmentioning
confidence: 89%
“…When the critical value of Ki-67 index was 10%, for both high expression (≥10%) and low expression (<10%), patients with BC show statistical differences in OS and recurrence-free survival (RFS) when there's low PR expression (<20%). In particular, patients with high Ki-67 expression and low PR expression had the poorest prognosis [20]. Similarly, Ki-67 index is signi cant to DFS judgment of patients with BC.…”
Section: Discussionmentioning
confidence: 89%
“…Ki-67 is an antigen associated with cell proliferation and generally less than 10% with benign tumors, but more than 10% with malignant tumors. In patients with invasive breast cancer, the higher Ki-67 expression, the faster the proliferation of cancer cells, and the greater the likelihood of metastasis (19)(20)(21)(22). As the Ki-67 level increases, cell growth increases, so the tumor cell density is higher, resulting in a decrease of the apparent diffusion coefficient.…”
Section: Discussionmentioning
confidence: 99%
“…Criscitiello et al investigated 1241 patients with Luminal B early stage breast cancer with 1-3 axillary positive nodes and found that patients with high Ki67 expression (>32%) could bene t from adjuvant chemotherapy in addition to HT [34]. Kang et al reported that patients with high Ki67 expression had poorer RFS and OS compared with those with low Ki67 expression (10% of cutoff) only when the PR was low [35]. Unfortunately, we did not test the cohort at this Ki67 level.…”
Section: Discussionmentioning
confidence: 99%